Bacterial Communities in Larval Diapause and Pupal Guts In the Bamboo Borer, Omphisa fuscidentalis Hampson - Phakamas Subta (Science Faculty of Chiang Mai University, 2019)
This study investigated bacterial diversity in the gut of diapausing larvae and pupae of bamboo borer (Omphisa fuscidentalis) in non-feeding stages by using culture dependent methods. The densities of culturable bacteria in guts of diapausing larvae were high in the foregut and hindgut and it was significantly higher than that from pupae (P<0.05). Genetic analysis of cultured, isolated bacteria revealed 33 sequences of 16S rRNA genes, from which the bacteria could be divided into three phyla groups, namely Gammaproteobacteria, Firmicutes and Bacteriodes. Current result therefore is the first report of gut bacteria in diapausing larval and pupal stages of O. fuscidentalis. metamorphosis from larvae to pupae and the diversity of bacteria in O. fuscidentalis is similar to many insects gut. Thus, gut bacteria in O. fuscidaentalis may provide larvae digestion and contribute nutrition.